Students’ Motivation in Learning English - Neng Aprilia Purnama; Neng Sri Rahayu; Rasi Yugafiati (PROJECT (Professional Journal of English Education), 2019)
Motivation is one of the most significant things in learning process. Without motivation, the purposes of learning is tough to be achieved. When learners have it in learning process, they will more understand with the materials, especially English. The goal of this study is to know how students’ motivation in learning English of eight grade at MTs Mathla’ul Anwar Sukaguna. This study used descriptive qualitative method. The data was carried out by using a questionnaire of students’ motivation which have ten items adapted from Clement, Dornyei, & Noels (1994) and used an interview which have five questions‎. The data were processed in the percentage and descriptive explanation. The main findings described that the learners are entirety highly motivated. Based on this study’s findings, students of eighth grade at MTs Mathla’ul Anwar have that motivation, it is based on the outcome of questionnaire and interview. From the output of questionnaire, most of students choose the agree statements. It means that students has an savor in learning English. Furthermore, the yield of interview expressed that students have highly interesting in learning English. But in this case, the teacher have to be more creative in using the media, strategy, or delivered material in teaching learning activity to improve students’ motivation.